Spatial, temporal, and inter-compartmental environmental monitoring of lipophilic pollutants by virtual organisms. (February 2021) - Pandelova, Marchela; Henkelmann, Bernhard; Lalah, Joseph O.; Norf, Helge; Schramm, Karl-Werner
Abstract: Sampling points belonging to the Harz National Park river system, Germany, were selected between the period of 2014 and 2017 for monitoring polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) in water, air, and sediment. Triolein-containing Virtual Organisms (VO) were employed to assess the levels of chemicals in water, air and triolein as surrogate for natural fat. To avoid overestimation of the concentrations 20 performance reference compounds (PRCs)-16 PRCs-PAHs and 4 PRCs-PCBs were covering the range of properties of native compounds. Results manifested the highest concentration of individual PAH as follows: 31 ng fluoranthene/L water, 3600 ng pyrene/g fat, 62 ng phenanthrene/m 3 air and 2800 ng fluoranthene/g dw sediment. All PCBs and OCPs values were below above mentioned PAH concentrations and far below EU-limit levels. Environmental partition of chemicals was investigated by calculating fugacity, suggesting a mass transport from water to air. Only quite volatile compounds such as hexachlorobutadiene showed higher fugacity in air. Ratios of sediment/water concentrations and log Kow within individual sampling periods at Holtemme River exhibited strong linear relationships. Interestingly, during summer months of the years water and fat contents well correlate to the flow rates of Holtemme River. Our results show that VO can be successfully used as a tool for ongoing exposure assessment studies and predictions of worst case levels in food and nutrition. Graphical abstract: Image 1 Highlights: Virtual Organisms are used to estimate the water (mass/L), air (mass/m 3 ) and fat (mass/g fat) contents of contaminants. The concentrations for individual PAHs, PCBs, OCPs in water, air, fat and sediment in Harz National Park are low. The calculated chemical fugacity suggests a mass transport from water to air. During the summer months water and fat contents may well correlated to the flow rates of the Holtemme River.